Development of diabetes does not alter behavioral and molecular circadian rhythms in a transgenic rat model of type 2 diabetes mellitus - Qian, Jingyi (Am J Physiol Endocrinol Metab, 2017)
Metabolic state and circadian clock function exhibit a complex bidirectional relationship. Circadian disruption increases propensity for metabolic dysfunction, whereas common metabolic disorders such as obesity and type 2 diabetes (T2DM) are associated with impaired circadian rhythms. Specifically, alterations in glucose availability and glucose metabolism have been shown to modulate clock gene expression and function in vitro; however, to date, it is unknown whether development of diabetes imparts deleterious effects on the suprachiasmatic nucleus (SCN) circadian clock and SCN-driven outputs in vivo. To address this question, we undertook studies in aged diabetic rats transgenic for human islet amyloid polypeptide, an established nonobese model of T2DM (HIP rat), which develops metabolic defects closely recapitulating those present in patients with T2DM. HIP rats were also cross-bred with a clock gene reporter rat model (Per1:luciferase transgenic rat) to permit assessment of the SCN and the peripheral molecular clock function ex vivo. Utilizing these animal models, we examined effects of diabetes on 1) behavioral circadian rhythms, 2) photic entrainment of circadian activity, 3) SCN and peripheral tissue molecular clock function, and 4) melatonin secretion. We report that circadian activity, light-induced entrainment, molecular clockwork, as well as melatonin secretion are preserved in the HIP rat model of T2DM. These results suggest that despite the well-characterized ability of glucose to modulate circadian clock gene expression acutely in vitro, SCN clock function and key behavioral and physiological outputs appear to be preserved under chronic diabetic conditions characteristic of nonobese T2DM.